Performance of concrete in aggressive environment - Aguiar, J. L. Barroso de (2008)
Surface treatments act as a barrier between the environment and the concrete, preventing or retarding the entry of harmful substances and cutting off the transportation path into concrete. The effectiveness of a surface protection preventing the permeation depends on how close and strongly connected are the resin molecules. This work intends to contribute to a better understanding of the performance of protected concrete in chemically aggressive environments, by presenting results of ion diffusion and resistance to aggressive solutions of several hydrophobic agents and coatings used to protect concrete. Three different types of surface protections were tested: silicone hydrophobic agent, acrylic and epoxy coatings. The obtained results indicate that the overall performance of epoxy resin was better than the other selected types of protections.